2010
DOI: 10.1590/s0104-42302010000200026
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and pathological staging of NSCLC: retrospective analysis of 291 cases

Abstract: Preoperative clinical staging presents limited efficacy for the correct staging of NSCLC patients from this sample of Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Cancer mortality rates began to decline in developed countries in the 1990s, but their behavior in developing countries is less well-known, which led Fonseca et al45 to re-examine the Brazilian situation finding that, as seen in developed countries, general cancer mortality rates tended to decline in Brazilian state capitals over the period 1980-2004, a tendency largely due to a decline in stomach cancer death rates for both genders. Younes et al46 evaluated the accuracy of preoperative clinical staging with computed tomography in predicting the correct pathological stage. And conclude that clinical staging presents limited efficacy for the correct staging of non-small cell lung cancer patients in a sample of the Brazilian population.…”
Section: Reviewmentioning
confidence: 99%
“…Cancer mortality rates began to decline in developed countries in the 1990s, but their behavior in developing countries is less well-known, which led Fonseca et al45 to re-examine the Brazilian situation finding that, as seen in developed countries, general cancer mortality rates tended to decline in Brazilian state capitals over the period 1980-2004, a tendency largely due to a decline in stomach cancer death rates for both genders. Younes et al46 evaluated the accuracy of preoperative clinical staging with computed tomography in predicting the correct pathological stage. And conclude that clinical staging presents limited efficacy for the correct staging of non-small cell lung cancer patients in a sample of the Brazilian population.…”
Section: Reviewmentioning
confidence: 99%
“…However, these factors are usually evaluated preoperatively by radiologic imaging tools. Although chest tomography (CT) and FDG-PET scan provide more detailed information about disease severity, more and more studies have revealed significant differences between clinical and pathological stage (13)(14)(15)(16)(17)(18)(19). In patients who have received neoadjuvant therapy, occult metastases and alterations to the tumor microenvironment by chemotherapy may interfere with the FDG uptake and lead to a false negative result.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related mortality in adults in many countries, especially in smokers [1,2]. There are small cell and non-small cell lung cancers (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…The TNM staging system is closely associated with prognosis. Metastatic disease, defined as stage IV, accounting for 10% to 20% of cases, has a median survival time of nine months and a five-year survival of about 1% [2]. The peak age for NSCLC is 50 years to 60 years [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation